Livestock Production - Javed, Khalid (IntechOpen, 2012)
Innumerable publications on livestock production are available in the world market. The book under discussion has not been produced to burden the market with another such publication rather it has been brought out employing a novice format to meet the requirements of students, researchers who are working in different parts of the world in different environments.